A copper-based catalyst for methanol cracking to produce hydrogen and a preparation method thereof
By using nano -phosphate as a carrier in the reorganized hydrogen catalyst in methanol water steam, and react with copper -manganese zinc salt, combined with solution gel process and high temperature burning, solve the problem of low temperature activity of existing catalysts and poor high temperature stability. , Achieve efficient methanol cracking hydrogenation effect.
Patent Information
- Application Number
- CN202411726902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing methanol water vapor reforming hydrogen-making copper-based catalysts have problems such as low-temperature hydrogen production activity, excessive copper content, high CO content in the reforming exhaust gas, and easy sintering and poor stability at high temperatures.
Using nano-phosphate as a carrier, through the response of amino siane coupling agent and ethyleine tethalcetic acid, to form a modified nanopensive acid, then react with the copper-manganese zinc salt solution to prepare nano-phosphate-copper manganese zinc oxides , And form a copper aluminum gel through the solid gel process, and eventually obtained the copper -based catalyst for the hydrogen -based hydrogen -based catalyst.
A methanol cracking hydrogen production catalyst with high low-temperature activity, low copper content, difficulty in sintering, and good high-temperature stability has been achieved, and the CO content in the reformed exhaust gas has also been significantly reduced.
Smart Images

Figure CN119186608B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper-based catalyst for producing hydrogen by cracking methanol and a preparation method thereof, belonging to the technical field of producing hydrogen by cracking methanol. Background Art
[0002] There are generally three methods for producing hydrogen by methanol cracking, namely, methanol steam reforming, methanol partial oxidation and methanol autothermal reforming. Among them, methanol steam reforming has attracted widespread attention due to its advantages such as low reforming temperature and low CO content in the product. At present, the catalyst used for methanol steam reforming to produce hydrogen is mainly copper-based catalyst, but copper-based catalysts still have low hydrogen production activity at low temperatures, and excessively increasing the copper content to improve the catalytic activity will lead to a high CO content in the reforming tail gas. At the same time, too high a copper content often leads to excessively large copper oxide crystals and the resulting problems of easy sintering at high temperatures and poor high temperature stability.
[0003] Chinese patent CN107824190A discloses a highly efficient copper-based catalyst for hydrogen production by decomposing methanol, wherein the catalyst is CuO, ZnO, Al2O3, M x O Y The weight percentage of each component is as follows: CuO is 10-60%, ZnO is 10-60%, Al2O3 is 5-50%, M x O Y The content of copper oxide in the catalyst is 1-10%, wherein the alkaline earth metal M is selected from one of Mg, Ca, Ce and Sr, and the preparation method is as follows: (1) the alumina carrier is modified by adding alkaline earth metal to prepare the Al-M modified carrier; (2) low molecular alcohol is added to the mother liquor of the modified carrier, and then active metal salt solution and alkaline precipitant are added to carry out precipitation reaction, and after the reaction, the catalyst is separated from the solid and liquid, washed, dried and roasted to obtain the catalyst. The catalyst obtained in this patent has a relatively high copper oxide content of 10-60%, and its heat resistance is not particularly good. After aging at 230°C and 280°C, the catalytic activity decreases by 3 to 15 percentage points. At the same time, the carbon monoxide content in the reformed tail gas is above 0.2%, which is not particularly ideal.
[0004] Chinese patent CN115888754A discloses a method for preparing a methanol reforming hydrogen production catalyst with a low copper content, and the preparation method is as follows: a low copper precursor, clay and an additive are mixed uniformly in a certain proportion to obtain a solid mixture, a pore-forming agent and an appropriate amount of water are added to the solid mixture, and after grinding, a 5mm diameter mold is used for tableting to obtain a catalyst precursor; then the precursor is roasted in an air atmosphere of 200~260℃ for 6h to obtain a methanol reforming hydrogen production catalyst with a low copper content. Although the copper content of the methanol reforming hydrogen production catalyst obtained in this patent is relatively low, it is also above 20%, which is not a particularly low copper content, and the highest methanol conversion rate is only 84.2%. After high-temperature aging, the decrease in methanol conversion rate is mostly above 10%.
[0005] From the above, we can see that the copper-based catalyst used for methanol steam reforming to produce hydrogen still has problems such as low hydrogen production activity at low temperatures, too high copper content and the resulting high CO content in the reforming tail gas, easy sintering at high temperatures, and poor high-temperature stability. Therefore, the development of copper-based catalysts for methanol cracking to produce hydrogen with high low-temperature activity, low copper content and not easy to sinter, good high-temperature stability, and low CO content in the reforming tail gas is of very important practical significance and value. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a copper-based catalyst for hydrogen production by methanol cracking and a preparation method thereof, so as to achieve the following invention objectives: to prepare a copper-based catalyst for hydrogen production by methanol cracking, which has high low-temperature activity, low copper content and is not easy to sinter, good high-temperature stability and low CO content in the reformed tail gas.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A copper-based catalyst for hydrogen production by methanol cracking and a preparation method thereof, wherein the copper-based catalyst for hydrogen production by methanol cracking has a copper oxide content of 7.5-14.3wt%, an initial performance of a methanol conversion rate of 97.1-98.2%, a hydrogen selectivity of 98.2-98.9%, and a CO content of 0.11-0.17% in the reformed tail gas, and a heat-resistant performance of a methanol conversion rate of 96.5-97.7%, a hydrogen selectivity of 97.6-98.3%, and a CO content of 0.15-0.19% in the reformed tail gas;
[0009] The following are further improvements to the above technical solution:
[0010] Step 1: Nano-zirconium phosphate modification
[0011] The nano zirconium phosphate is dried in an oven at 100-120°C for 8-12 hours, cooled to room temperature and added to a high-speed dispersion kettle, then anhydrous ethanol is added, the dispersion rate is controlled at 8000-13000 rpm, and the dispersion rate is reduced to 1000-2000 rpm after high-speed dispersion for 6-13 hours, then the temperature is raised and kept constant at 50-70°C, and an amino-containing silane coupling agent is added under condensation reflux state, and the dispersion is stirred and reacted for 5-9 hours, and then centrifuged to obtain silane-coupled nano zirconium phosphate, the silane-coupled nano zirconium phosphate is placed in a clean high-speed dispersion kettle, and then deionized water is added, the dispersion rate is controlled at 8000-11000 rpm, and the dispersion rate is reduced to 900-1500 rpm after high-speed dispersion for 8-15 hours, and then the temperature is raised and kept constant at 90-100°C, and then ethylenediaminetetraacetic acid is added, and the dispersion is stirred and reacted at constant temperature for 10-18 hours, and then cooled to room temperature, and centrifuged to obtain modified nano zirconium phosphate;
[0012] The particle size of the nano zirconium phosphate is 10-100 nm;
[0013] The amino-containing silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane;
[0014] The mass ratio of the nano zirconium phosphate, anhydrous ethanol and amino-containing silane coupling agent is 30-80:140-250:8-20;
[0015] The mass ratio of the silane-coupled nano zirconium phosphate, deionized water and ethylenediaminetetraacetic acid is 20-60:90-180:8-25.
[0016] Step 2: Preparation of Nano-Zirconium Phosphate-Copper Manganese Zinc Oxide
[0017] The modified nano zirconium phosphate is added to a high-speed dispersing kettle, and then a copper-manganese-zinc salt solution is added. The amount of the copper-manganese-zinc salt solution added is the minimum limit to completely immerse the modified nano zirconium phosphate. After controlling the dispersion rate at 7000-12000 rpm and dispersing at high speed for 8-15 hours, the dispersing paddle is turned off, and the mixture is allowed to stand for immersion and complexation for 20-28 hours, and then centrifuged. The separated solid is placed in a muffle furnace, and the mixture is heated to 300-450° C. at a heating rate of 1-3° C. / min, and then calcined at a constant temperature for 2-5 hours to obtain nano zirconium phosphate-copper-manganese-zinc oxide.
[0018] The copper-manganese-zinc salt solution is a mixed aqueous solution of copper nitrate, manganese nitrate and zinc nitrate, wherein the mass ratio of copper nitrate, manganese nitrate, zinc nitrate and deionized water is 10-25:40-90:30-80:120-200.
[0019] Step 3: Preparation of copper-aluminum-zirconium gel
[0020] A mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide and polyvinyl pyrrolidone are added to a high-speed dispersion kettle, and the dispersion rate is controlled at 6000-9000 rpm. After high-speed dispersion for 5-10 hours, the dispersion rate is reduced to 900-1600 rpm, and then ammonia water with a mass concentration of 9-18wt% is added dropwise at a rate of 0.1-0.9g / min until the pH value of the solution reaches 9-10 to obtain a copper-aluminum sol. Then, the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone are added to the high-speed dispersion kettle. In a dispersing kettle, the dispersion rate is controlled at 6000-9000 rpm, and after high-speed dispersion for 7-11 hours, the dispersion rate is reduced to 900-1600 rpm, and then ammonia water with a mass concentration of 9-18wt% is added dropwise at a rate of 0.1-0.9 g / min until the pH value of the solution reaches 9-10 to obtain zirconium sol, and then the copper aluminum sol and the zirconium sol are put into a mixing kettle at a mass ratio of 1:0.8-1.3, and the stirring rate is controlled at 900-1900 rpm. After stirring and mixing for 5-14 hours, the mixture is allowed to stand for aging for 30-50 hours to obtain a copper aluminum zirconium gel;
[0021] The model of the polyvinyl pyrrolidone is K30, and the molecular weight is 43000-55000 g / mol;
[0022] The mixed aqueous solution of aluminum chloride and copper chloride, wherein the mass fraction of aluminum chloride is 10-35wt%, and the mass fraction of copper chloride is 6-25wt%;
[0023] The mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide, and polyvinyl pyrrolidone are fed in a mass ratio of 80-190:20-100:0.5-4;
[0024] The mass ratio of the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone is 60-160:2-9:0.5-1:0.5-2;
[0025] In the zirconium oxychloride aqueous solution, the mass fraction of zirconium oxychloride is 10-40wt%;
[0026] The particle size of the nano magnesium oxalate powder is 10-100 nm;
[0027] The stabilizer Y2O3 is powdered nano Y2O3 with a particle size of 10-100 nm.
[0028] Step 4: Post-processing
[0029] The copper-aluminum-zirconium gel is washed with deionized water for 3 to 6 times, the mass of deionized water used for each washing is equal to the mass of the copper-aluminum-zirconium gel, and then washed with anhydrous ethanol for 2 to 4 times, the mass of anhydrous ethanol used for each washing is equal to the mass of the copper-aluminum-zirconium gel, and then the gel is placed in a dry and dust-free room temperature environment for 72 to 100 hours, then placed in an oven, dried at 90 to 110° C. for 10 to 19 hours, placed in a dry environment to cool to room temperature, and then ground into 300 to 800 mesh powder in a dry environment, and then the powder is placed in a muffle furnace, and the temperature is increased and maintained at a constant temperature to 700 to 950° C. at a heating rate of 2 to 10° C. / min, and then cooled to room temperature after being calcined at a constant temperature for 1 to 5 hours, to obtain a copper-based catalyst for hydrogen production by methanol cracking.
[0030] Compared with the prior art, the present invention achieves the following beneficial effects:
[0031] 1. The present invention uses nano zirconium phosphate as a carrier of a copper-based catalyst. Nano zirconium phosphate itself has the characteristics of high mechanical strength, high thermal stability, and high chemical stability. It also has a very large adsorption area and a layered mesoporous structure. The inner surface of the layered mesoporous structure contains a large number of active hydroxyl groups. The present invention first uses an amino-containing silane coupling agent to react with these hydroxyl groups in the nano zirconium phosphate mesoporous structure. The terminal hydroxyl groups on the inner surface of the nano zirconium phosphate mesoporous structure are replaced by alkaline amino groups. Then, these amino groups react with ethylenediaminetetraacetic acid to form a salt by acid-base neutralization. The ends of the inner surface of the nano zirconium phosphate mesoporous structure are eventually covered with terminal carboxyl groups of ethylenediaminetetraacetic acid. This terminal chemical structure has a very strong complexing effect on divalent metal ions. Therefore, after preparing the modified nano zirconium phosphate of the above structure, the present invention further complexes the three divalent metal ions of copper, manganese, and zinc, and preliminarily obtains the oxides of the three metals of copper, manganese, and zinc through low-temperature calcination. Through the complexing effect of ethylenediaminetetraacetic acid and its terminal carboxyl groups, the oxides of the three metals of copper, manganese, and zinc are complexed and adsorbed on the inner surface of the nano zirconium phosphate mesoporous structure. The three divalent metal ions of copper, manganese and zinc are a slow chemical adsorption and complexation process with a slow reaction rate and a competitive relationship between the complexation and adsorption of the three metal ions of copper, manganese and zinc. This can promote the uniform adsorption of the three metal ions on the inner surface of the nano-zirconium phosphate mesoporous structure, and avoid the excessively high local adsorption and complexation concentration of copper ions on the inner surface of the nano-zirconium phosphate mesoporous structure during the subsequent calcination process, which leads to the generated copper oxide crystal size being too large, thereby greatly reducing the catalytic effect of copper oxide and reducing the thermal stability. On the other hand, this uniform adsorption and complexation process, combined with the subsequent preliminary low-temperature calcination and high-temperature calcination in the post-treatment step, the crystals of the oxides formed by the three metals of copper, manganese and zinc will be maximally refined and amorphized, which greatly increases the number of active sites for the catalytic reaction. At the same time, the refinement and amorphization of the three metal oxides of copper, manganese and zinc will also maximize the binding force between the three metal oxides and nano-zirconium phosphate, thereby greatly improving the high-temperature thermal stability of the copper-based catalyst for methanol cracking hydrogen production.
[0032] 2. The present invention uses a sol-gel process, selects aluminum trichloride, copper chloride and zirconium oxychloride as raw materials, uses polyvinyl pyrrolidone as a dispersant, firstly uniformly disperses nano zirconium phosphate-copper manganese zinc oxide and nano magnesium oxalate into an aluminum copper salt aqueous solution and a zirconium salt aqueous solution respectively, then drips ammonia water to prepare corresponding copper aluminum sol and zirconium sol, and after the two sols are uniformly mixed, they are subjected to a gel reaction process, standing, aging and other steps to obtain an aged copper aluminum zirconium gel, and then subjected to washing, drying, grinding, calcining and other steps to finally obtain a micro-nano porous catalytic material with copper aluminum zirconium oxide as an outer coating layer and nano zirconium phosphate-copper manganese zinc oxide as an inner core, and a microstructure similar to a three-dimensional network sintered structure of oxide ceramics. The micro-nano pores formed by the above-mentioned preparation process are very fine and uniform, and the distribution of metal oxides on the inner wall surface of the micro-nano pores is very uniform, which provides a larger catalytic active adsorption area and also increases more catalytic active sites, so that the copper-based catalyst for hydrogen production by methanol cracking has better low-temperature catalytic activity, higher methanol conversion rate and higher hydrogen selectivity;
[0033] 3. In the preparation step of the copper-aluminum-zirconium gel of the present invention, nano-magnesium oxalate is added to the zirconium sol. Through the subsequent process steps, the magnesium oxalate is finally dispersed into the copper-aluminum-zirconium gel in nanometer scale. In the high-temperature constant-temperature calcination process of the post-treatment, the magnesium oxalate will slowly decompose to generate carbon dioxide and magnesium oxide, and finally remain in the copper-based catalyst for hydrogen production by methanol cracking in the form of nano-magnesium oxide. During the process of constant-temperature calcination of magnesium oxalate powder to generate magnesium oxide, some chemical modification may occur with the oxide generated after calcination of the copper-aluminum-zirconium gel and nano-zirconium phosphate-copper manganese zinc oxide, so that the magnesium oxide can play a non- The copper-aluminum-zirconium oxide has a very critical catalytic effect, thereby greatly improving the low-temperature activity and high-temperature stability of the copper-based catalyst for hydrogen production by methanol cracking. In addition, during the high-temperature constant-temperature calcination process, copper-aluminum-zirconium oxide forms an outer coating layer on the surface of nano zirconium phosphate-copper manganese zinc oxide, and the carbon dioxide released by the slow decomposition of magnesium oxalate can leave a certain amount of micropores in the outer coating layer, which can avoid the dense wrapping of the nano zirconium phosphate-copper manganese zinc oxide by the coating layer, and maintain the full exposure of the active sites of the catalytic reaction of the nano zirconium phosphate-copper manganese zinc oxide itself, so as to avoid the reduction of catalytic efficiency due to the dense coating of the active sites;
[0034] 4. The copper-based catalyst for methanol cracking and hydrogen production obtained by the present invention has a copper oxide content of 7.5-14.3wt%, initial performance: methanol conversion rate 97.1-98.2%, hydrogen selectivity 98.2-98.9%, CO content in reformed tail gas 0.11-0.17%, and heat-resistant performance: methanol conversion rate 96.5-97.7%, hydrogen selectivity 97.6-98.3%, CO content in reformed tail gas 0.15-0.19%. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope photograph of the copper-based catalyst for hydrogen production by methanol cracking obtained in Example 1, with its surface magnified 100,000 times;
[0036] Figure 2 This is a scanning electron microscope photograph of the copper-based catalyst for hydrogen production by methanol cracking obtained in Example 2, with its surface magnified 100,000 times;
[0037] Figure 3 This is a transmission electron microscope photograph of the cross section of the copper-based catalyst for hydrogen production by cracking methanol obtained in Example 1, magnified 300,000 times;
[0038] Figure 4 This is a transmission electron microscope photograph of the cross section of the copper-based catalyst for hydrogen production by cracking methanol obtained in Example 2, magnified 300,000 times. DETAILED DESCRIPTION
[0039] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0040] Example 1: A method for preparing a copper-based catalyst for hydrogen production by methanol cracking
[0041] Step 1: Nano-zirconium phosphate modification
[0042] The nano-zirconium phosphate was dried in an oven at 115° C. for 9 hours, cooled to room temperature and added to a high-speed dispersion kettle, then anhydrous ethanol was added, the dispersion rate was controlled at 11000 rpm, and the dispersion rate was reduced to 1600 rpm after 10 hours of high-speed dispersion, then the temperature was raised and kept constant at 65° C., and an amino-containing silane coupling agent was added under condensation reflux state, and the dispersion was stirred and reacted for 8 hours, and then centrifuged to obtain silane-coupled nano-zirconium phosphate, the silane-coupled nano-zirconium phosphate was put into a clean high-speed dispersion kettle, and then deionized water was added, the dispersion rate was controlled at 9000 rpm, and the dispersion rate was reduced to 1100 rpm after 13 hours of high-speed dispersion, and then the temperature was raised and kept constant at 98° C., and then ethylenediaminetetraacetic acid was added, and the dispersion was stirred and reacted at a constant temperature for 15 hours, and then cooled to room temperature and centrifuged to obtain modified nano-zirconium phosphate;
[0043] The particle size of the nano zirconium phosphate is 40 nm;
[0044] The amino-containing silane coupling agent is γ-aminopropyltriethoxysilane;
[0045] The mass ratio of the nano zirconium phosphate, anhydrous ethanol and amino-containing silane coupling agent is 60:210:14;
[0046] The mass ratio of the silane-coupled nano-zirconium phosphate, deionized water and ethylenediaminetetraacetic acid is 50:130:15.
[0047] Step 2: Preparation of Nano-Zirconium Phosphate-Copper Manganese Zinc Oxide
[0048] Add the modified nano zirconium phosphate to a high-speed dispersing kettle, then add a copper-manganese-zinc salt solution, the amount of the copper-manganese-zinc salt solution added is the minimum limit to completely immerse the modified nano zirconium phosphate, control the dispersion rate at 11000 rpm, high-speed disperse for 13 hours, turn off the dispersing paddle, let it stand for immersion and complexation for 26 hours, centrifuge, put the separated solid into a muffle furnace, heat it to 400°C at a heating rate of 2°C / min, and then calcine at a constant temperature for 4 hours to obtain nano zirconium phosphate-copper-manganese-zinc oxide;
[0049] The copper-manganese-zinc salt solution is a mixed aqueous solution of copper nitrate, manganese nitrate and zinc nitrate, wherein the mass ratio of copper nitrate, manganese nitrate, zinc nitrate and deionized water is 18:70:60:180.
[0050] Step 3: Preparation of copper-aluminum-zirconium gel
[0051] A mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide and polyvinyl pyrrolidone were added into a high-speed dispersion kettle, and the dispersion rate was controlled at 7000 rpm. After high-speed dispersion for 8 hours, the dispersion rate was reduced to 1300 rpm, and then ammonia water with a mass concentration of 14 wt% was added dropwise at a rate of 0.7 g / min until the pH value of the solution reached 9.6 to obtain a copper-aluminum sol. Then, the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone were added into the kettle. Alkyl ketone is added into a high-speed dispersing kettle, and the dispersing rate is controlled at 8000 rpm. After high-speed dispersing for 10 hours, the dispersing rate is reduced to 1300 rpm, and then ammonia water with a mass concentration of 14wt% is added dropwise at a rate of 0.7g / min until the pH value of the solution reaches 9.6 to obtain zirconium sol, and then copper aluminum sol and zirconium sol are put into a mixing kettle at a mass ratio of 1:1, and the stirring rate is controlled at 1200 rpm. After stirring and mixing for 10 hours, the mixture is allowed to stand for aging for 45 hours to obtain copper aluminum zirconium gel;
[0052] The model of the polyvinyl pyrrolidone is K30, and the molecular weight is 48000 g / mol;
[0053] The mixed aqueous solution of aluminum chloride and copper chloride, wherein the mass fraction of aluminum chloride is 28wt%, and the mass fraction of copper chloride is 20wt%;
[0054] The mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide, and polyvinyl pyrrolidone are fed in a mass ratio of 150:60:2;
[0055] The mass ratio of the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone is 120:5:0.8:1;
[0056] In the zirconium oxychloride aqueous solution, the mass fraction of zirconium oxychloride is 30wt%;
[0057] The particle size of the nano magnesium oxalate powder is 40 nm;
[0058] The stabilizer Y2O3 is powdered nano Y2O3 with a particle size of 30 nm.
[0059] Step 4: Post-processing
[0060] The copper-aluminum-zirconium gel was washed with deionized water for 5 times, the mass of deionized water used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then washed with anhydrous ethanol for 3 times, the mass of anhydrous ethanol used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then the gel was placed in a dry and dust-free environment at room temperature for 90 hours, and then placed in an oven and dried at 105°C for 15 hours, and then placed in a dry environment to cool to room temperature, and then ground into 700-mesh powder in a dry environment, and then the powder was placed in a muffle furnace, and the temperature was increased and maintained at a constant temperature to 800°C at a heating rate of 4°C / min, and after constant temperature calcination for 4 hours, it was cooled to room temperature to obtain a copper-based catalyst for methanol cracking to produce hydrogen.
[0061] Example 2: A method for preparing a copper-based catalyst for hydrogen production by methanol cracking
[0062] Step 1: Nano-zirconium phosphate modification
[0063] The nano zirconium phosphate was dried in an oven at 100°C for 8 hours, cooled to room temperature and added to a high-speed dispersion kettle, then anhydrous ethanol was added, the dispersion rate was controlled at 8000 rpm, and the dispersion rate was reduced to 1000 rpm after 6 hours of high-speed dispersion, then the temperature was raised and kept constant at 50°C, and an amino-containing silane coupling agent was added under condensation reflux state, and the dispersion was stirred and reacted for 5 hours, and then centrifuged to obtain silane-coupled nano zirconium phosphate, the silane-coupled nano zirconium phosphate was put into a clean high-speed dispersion kettle, and then deionized water was added, the dispersion rate was controlled at 8000 rpm, and the dispersion rate was reduced to 900 rpm after 8 hours of high-speed dispersion, and then the temperature was raised and kept constant at 90°C, and then ethylenediaminetetraacetic acid was added, and the dispersion was stirred and reacted at a constant temperature for 10 hours, and then cooled to room temperature, and centrifuged to obtain modified nano zirconium phosphate;
[0064] The particle size of the nano zirconium phosphate is 10 nm;
[0065] The amino-containing silane coupling agent is γ-aminopropyltrimethoxysilane;
[0066] The mass ratio of the nano zirconium phosphate, anhydrous ethanol and amino-containing silane coupling agent is 30:140:8;
[0067] The mass ratio of the silane-coupled nano-zirconium phosphate, deionized water and ethylenediaminetetraacetic acid is 20:90:8.
[0068] Step 2: Preparation of Nano-Zirconium Phosphate-Copper Manganese Zinc Oxide
[0069] The modified nano zirconium phosphate is added to a high-speed dispersing kettle, and then a copper-manganese-zinc salt solution is added. The amount of the copper-manganese-zinc salt solution added is the minimum limit to completely immerse the modified nano zirconium phosphate. After controlling the dispersion rate at 7000 rpm and dispersing at high speed for 8 hours, the dispersing paddle is turned off, and the mixture is allowed to stand for immersion and complexation for 20 hours, and then centrifuged. The separated solid is placed in a muffle furnace, and the mixture is heated to 300° C. at a heating rate of 1° C. / min, and then calcined at a constant temperature for 2 hours to obtain nano zirconium phosphate-copper-manganese-zinc oxide.
[0070] The copper-manganese-zinc salt solution is a mixed aqueous solution of copper nitrate, manganese nitrate and zinc nitrate, wherein the mass ratio of copper nitrate, manganese nitrate, zinc nitrate and deionized water is 10:40:30:120.
[0071] Step 3: Preparation of copper-aluminum-zirconium gel
[0072] A mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide and polyvinyl pyrrolidone are added to a high-speed dispersing kettle, and the dispersing rate is controlled at 6000 rpm. After high-speed dispersing for 5 hours, the dispersing rate is reduced to 900 rpm, and then ammonia water with a mass concentration of 9wt% is added dropwise at a rate of 0.1 g / min until the pH value of the solution reaches 9, thereby obtaining a copper-aluminum sol. Then, a zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone are added to a high-speed dispersing kettle, and the dispersing rate is controlled at 6000 rpm. After high-speed dispersing for 7 hours, the dispersing rate is reduced to 900 rpm, and then ammonia water with a mass concentration of 9wt% is added dropwise at a rate of 0.1 g / min until the pH value of the solution reaches 9, thereby obtaining a zirconium sol. Then, the copper-aluminum sol and the zirconium sol are put into a mixing kettle at a mass ratio of 1:0.8, and the stirring rate is controlled at 900 rpm. After stirring and mixing for 5 hours, the mixture is allowed to stand for aging for 30 hours to obtain a copper-aluminum-zirconium gel.
[0073] The model of the polyvinyl pyrrolidone is K30, and the molecular weight is 43000 g / mol;
[0074] The mixed aqueous solution of aluminum chloride and copper chloride, wherein the mass fraction of aluminum chloride is 10wt%, and the mass fraction of copper chloride is 6wt%;
[0075] The mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide, and polyvinyl pyrrolidone are fed in a mass ratio of 80:20:0.5;
[0076] The mass ratio of the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone is 60:2:0.5:0.5;
[0077] In the zirconium oxychloride aqueous solution, the mass fraction of zirconium oxychloride is 10wt%;
[0078] The particle size of the nano magnesium oxalate powder is 10 nm;
[0079] The stabilizer Y2O3 is powdered nano Y2O3 with a particle size of 10 nm.
[0080] Step 4: Post-processing
[0081] The copper-aluminum-zirconium gel was washed with deionized water for three times, the mass of deionized water used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then washed with anhydrous ethanol for two times, the mass of anhydrous ethanol used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then the gel was placed in a dry and dust-free environment at room temperature for 72 hours, and then placed in an oven and dried at 90°C for 10 hours, and then placed in a dry environment to cool to room temperature, and then ground into 300-mesh powder in a dry environment, and then the powder was placed in a muffle furnace, and the temperature was increased and maintained at a constant temperature to 700°C at a heating rate of 2°C / min, and after constant temperature calcination for 1 hour, it was cooled to room temperature to obtain a copper-based catalyst for methanol cracking to produce hydrogen.
[0082] Example 3: Preparation method of a copper-based catalyst for hydrogen production by methanol cracking
[0083] Step 1: Nano-zirconium phosphate modification
[0084] The nano-zirconium phosphate was dried in an oven at 120° C. for 12 hours, cooled to room temperature and added to a high-speed dispersion kettle, then anhydrous ethanol was added, the dispersion rate was controlled at 13,000 rpm, and the dispersion rate was reduced to 2,000 rpm after 13 hours of high-speed dispersion, then the temperature was raised and kept constant at 70° C., and an amino-containing silane coupling agent was added under condensation reflux state, and the dispersion was stirred and reacted for 9 hours, and then centrifuged to obtain silane-coupled nano-zirconium phosphate, the silane-coupled nano-zirconium phosphate was put into a clean high-speed dispersion kettle, and then deionized water was added, the dispersion rate was controlled at 11,000 rpm, and the dispersion rate was reduced to 1,500 rpm after 15 hours of high-speed dispersion, then the temperature was raised and kept constant at 100° C., then ethylenediaminetetraacetic acid was added, the dispersion was stirred and reacted at a constant temperature for 18 hours, and then the mixture was cooled to room temperature and centrifuged to obtain modified nano-zirconium phosphate;
[0085] The particle size of the nano zirconium phosphate is 100 nm;
[0086] The amino-containing silane coupling agent is N,N-diethyl-3-aminopropyltrimethoxysilane;
[0087] The mass ratio of the nano zirconium phosphate, anhydrous ethanol and amino-containing silane coupling agent is 80:250:20;
[0088] The mass ratio of the silane-coupled nano-zirconium phosphate, deionized water and ethylenediaminetetraacetic acid is 60:180:25.
[0089] Step 2: Preparation of Nano-Zirconium Phosphate-Copper Manganese Zinc Oxide
[0090] The modified nano zirconium phosphate is added to a high-speed dispersing kettle, and then a copper-manganese-zinc salt solution is added. The amount of the copper-manganese-zinc salt solution added is the minimum limit to completely immerse the modified nano zirconium phosphate. After controlling the dispersion rate at 12,000 rpm and dispersing at high speed for 15 hours, the dispersing paddle is turned off, and the mixture is allowed to stand for immersion and complexation for 28 hours, and then centrifuged. The separated solid is placed in a muffle furnace, heated to 450° C. at a heating rate of 3° C. / min, and then calcined at a constant temperature for 5 hours to obtain nano zirconium phosphate-copper-manganese-zinc oxide.
[0091] The copper-manganese-zinc salt solution is a mixed aqueous solution of copper nitrate, manganese nitrate and zinc nitrate, wherein the mass ratio of copper nitrate, manganese nitrate, zinc nitrate and deionized water is 25:90:80:200.
[0092] Step 3: Preparation of copper-aluminum-zirconium gel
[0093] A mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide and polyvinyl pyrrolidone were added into a high-speed dispersion kettle, and the dispersion rate was controlled at 9000 rpm. After high-speed dispersion for 10 hours, the dispersion rate was reduced to 1600 rpm, and then ammonia water with a mass concentration of 18wt% was added dropwise at a rate of 0.9g / min until the pH value of the solution reached 10 to obtain a copper-aluminum sol. Then, the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone were added into the kettle. Ketone was added into a high-speed dispersing kettle, and the dispersing rate was controlled at 9000 rpm. After high-speed dispersing for 11 hours, the dispersing rate was reduced to 1600 rpm, and then ammonia water with a mass concentration of 18wt% was added dropwise at a rate of 0.9g / min until the pH value of the solution reached 10 to obtain zirconium sol, and then copper aluminum sol and zirconium sol were put into a mixing kettle at a mass ratio of 1:1.3, and the stirring rate was controlled at 1900 rpm. After stirring and mixing for 14 hours, the mixture was allowed to stand for 50 hours to obtain copper aluminum zirconium gel;
[0094] The model of the polyvinyl pyrrolidone is K30, and the molecular weight is 55000 g / mol;
[0095] The mixed aqueous solution of aluminum chloride and copper chloride, wherein the mass fraction of aluminum chloride is 35wt%, and the mass fraction of copper chloride is 25wt%;
[0096] The mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide, and polyvinyl pyrrolidone are fed in a mass ratio of 190:100:4;
[0097] The mass ratio of the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone is 160:9:1:2;
[0098] In the zirconium oxychloride aqueous solution, the mass fraction of zirconium oxychloride is 40wt%;
[0099] The particle size of the nano magnesium oxalate powder is 100 nm;
[0100] The stabilizer Y2O3 is powdered nano Y2O3 with a particle size of 100 nm.
[0101] Step 4: Post-processing
[0102] The copper-aluminum-zirconium gel was washed with deionized water for 6 times, the mass of deionized water used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then washed with anhydrous ethanol for 4 times, the mass of anhydrous ethanol used for each washing was equal to the mass of the copper-aluminum-zirconium gel, and then the gel was placed in a dry and dust-free environment at room temperature for 100 hours, and then placed in an oven, dried at 110°C for 19 hours, and then placed in a dry environment to cool to room temperature, and then ground into 800-mesh powder in a dry environment, and then the powder was placed in a muffle furnace, and the temperature was increased and maintained at a constant temperature to 950°C at a heating rate of 10°C / min, and after being calcined at a constant temperature for 5 hours, it was cooled to room temperature to obtain a copper-based catalyst for methanol cracking to produce hydrogen.
[0103] Example 4: Preparation method of a copper-based catalyst for hydrogen production by methanol cracking
[0104] Step 1: Nano-zirconium phosphate modification
[0105] The amino-containing silane coupling agent is N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and the other operations are the same as in Example 1;
[0106] The operations of steps 2, 3 and 4 are the same as those of Example 1.
[0107] Comparative Example 1: Based on Example 1, in step 2, in the preparation of nano zirconium phosphate-copper manganese zinc oxide, no manganese zinc is added to the copper manganese zinc salt solution, that is, 70 parts of manganese nitrate and 60 parts of zinc nitrate are replaced by 130 parts of copper nitrate in equal amounts, and the specific operation is as follows:
[0108] The operation of step 1 is the same as that of embodiment 1;
[0109] Step 2: Preparation of Nano-Zirconium Phosphate-Copper Manganese Zinc Oxide
[0110] 70 parts of manganese nitrate and 60 parts of zinc nitrate were replaced by 130 parts of copper nitrate, and the other operations were the same as in Example 1;
[0111] The operations of steps 3 and 4 are the same as those of Example 1.
[0112] Comparative Example 2: Based on Example 1, in step 3, preparation of copper-aluminum-zirconium gel, no nano magnesium oxalate powder was added to the zirconium sol, and 5 parts of nano magnesium oxalate powder were replaced by 5 parts of zirconium oxychloride aqueous solution in equal amounts. The specific operation was as follows:
[0113] The operations of steps 1 and 2 are the same as those of Example 1;
[0114] Step 3: Preparation of copper-aluminum-zirconium gel
[0115] The mass ratio of the zirconium oxychloride aqueous solution, the stabilizer Y2O3 and the polyvinyl pyrrolidone is 125:0.8:1, and the other operations are the same as in Example 1;
[0116] The operation of step 4 is the same as that of embodiment 1.
[0117] Performance Testing:
[0118] The catalytic activity of the copper-based catalyst for hydrogen production by methanol cracking obtained in Examples 1, 2, 3, 4 and Comparative Examples 1 and 2 was tested by the following test method: the activity of the catalyst was evaluated in a micro fixed bed reactor. The catalyst loading was 5.0 g, the pressure was 0.3 MPa, and the mass space velocity was 2.5 h -1 , the raw material reaction liquid with a mass ratio of H2O / CH3OH of 1:1, the evaluation temperature is 250℃, and the result after the reaction is stable for 12h is the initial test performance; then the temperature is raised to 330℃ for heat resistance for 12h, and then restored to the above initial test activity evaluation conditions. The result after stabilization for 10h is called the high temperature resistant reaction activity, and the product is analyzed by gas-liquid chromatography; Determination of copper oxide content in the catalyst: accurately weigh 1.00g of catalyst, dissolve it in 10% nitric acid solution, and finally make up the volume in a 1000ml volumetric flask, and the above solution is subjected to ICP-MS to determine the copper concentration and then calculated, unit: wt% (mass fraction); specific test results are shown in Table 1:
[0119] Table 1
[0120]
[0121] From the data in Table 1, it can be seen that the initial performance and heat-resistant performance of the copper-based catalyst for hydrogen production by methanol cracking obtained in Examples 1, 2, 3, and 4 are all above 96.5% in methanol conversion, above 97.6% in hydrogen selectivity, and below 0.2% in CO content in the reformed tail gas. Moreover, the highest copper oxide content is only 14.3%, which shows that the copper-based catalyst for hydrogen production by methanol cracking prepared by the present invention has excellent characteristics such as high low-temperature activity, low copper content and not easy to sinter, good high-temperature stability, and low CO content in the reformed tail gas; in Comparative Example 1, the nano During the preparation of zirconium phosphate-copper manganese zinc oxide, no zinc and manganese salts are added, and only copper salts are contained. The copper-based catalyst for methanol cracking and hydrogen production prepared in this way has a greatly increased copper oxide content. The copper oxide content of comparative example 1 reaches 35.7%, which also confirms this point. Due to the greatly increased copper oxide content, the methanol conversion rate of comparative example 1 is relatively high, up to 98.9%, but the hydrogen selectivity decreases relatively significantly, down to 97.3%, and the corresponding CO content in the reformed tail gas increases to 0.29%, and the catalytic performance of comparative example 1 after heat resistance is sharply reduced, and the reformed tail gas is The CO content in the gas is as high as 3.48%, which shows that the present invention prepares nano zirconium phosphate-copper manganese zinc oxide and uses copper, manganese and zinc three oxides to replace single copper oxide. This method of reducing the copper oxide content can improve the low-temperature activity and high-temperature stability of the copper-based catalyst for hydrogen production by methanol cracking under the premise of low copper content; in the preparation step of copper-aluminum zirconium gel in Comparative Example 2, magnesium oxalate is not added. The initial performance of Comparative Example 2, in terms of methanol conversion rate, hydrogen selectivity, and CO content in the reforming tail gas, are all reduced to the lowest values among all embodiments and comparative examples, and the decline in heat-resistant performance, like the initial performance, is also reduced to the lowest value among all embodiments and comparative examples, which shows that magnesium oxalate plays a vital role in improving the low-temperature activity and high-temperature stability of the copper-based catalyst for hydrogen production by methanol cracking. This may be because the magnesium oxide generated after the constant temperature calcination of magnesium oxalate powder has certain chemical modification effects on the oxide generated after the calcination of copper-aluminum zirconium gel and the nano zirconium phosphate-copper manganese zinc oxide, so that the magnesium oxide can play a very critical co-catalytic role, thereby greatly improving the low-temperature activity and high-temperature stability of the copper-based catalyst for hydrogen production by methanol cracking.
[0122] Attached Figure 1 and attached Figure 2 The copper-based catalysts for hydrogen production by methanol cracking obtained in Example 1 and Example 2 are scanning electron microscope photos of their surfaces magnified 100,000 times. The microscopic morphology of the catalysts shown in the two photos is roughly similar. It can be clearly seen that the microscopic morphology is a three-dimensional network structure similar to that of oxide sintered ceramics. Figure 1 The particle size in the Figure 2 The particle size of the nano zirconium phosphate added in Example 1 is 40 nm, and the particle size of the nano zirconium phosphate added in Example 2 is 10 nm. This also shows that the attached Figure 1 and attached Figure 2 The interconnected and sintered nano-scale particles shown in the figure are formed by nano-zirconium phosphate-copper manganese zinc oxide coated with copper aluminum zirconium gel, which is then bonded and sintered to form a three-dimensional network-like oxide ceramic sintered body structure.
[0123] Attached Figure 3 and attached Figure 4 The copper-based catalysts for hydrogen production from methanol cracking obtained in Example 1 and Example 2 are transmission electron microscope photographs of their cross-sections magnified 300,000 times, and the black areas in the two figures are transmission images of fine-grained copper oxide. It can be clearly seen from the two figures that the black areas are relatively small and the distribution is relatively dispersed and uniform, which indicates that the copper content in the copper-based catalysts for hydrogen production from methanol cracking obtained in Example 1 and Example 2 is relatively low and the distribution of copper oxide in the catalyst is very uniform.
[0124] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a copper-based catalyst for hydrogen production by methanol cracking, characterized in that: The preparation method of the copper-based catalyst for methanol cracking to produce hydrogen comprises four steps: modification of nano zirconium phosphate, preparation of nano zirconium phosphate-copper manganese zinc oxide, preparation of copper aluminum zirconium gel, and post-treatment; The nano zirconium phosphate modification comprises drying the nano zirconium phosphate in an oven at 100-120° C. for 8-12 hours, cooling to room temperature, adding the nano zirconium phosphate to a high-speed dispersion kettle, and then adding anhydrous ethanol, controlling the dispersion rate at 8000-13000 rpm, and reducing the dispersion rate to 1000-2000 rpm after high-speed dispersion for 6-13 hours, then heating and maintaining the temperature at 50-70° C., adding an amino silane coupling agent under condensation reflux, dispersing and stirring the reaction for 5-9 hours, and centrifuging. Separate to obtain silane-coupled nano zirconium phosphate, put the silane-coupled nano zirconium phosphate into a clean high-speed dispersion kettle, then add deionized water, control the dispersion rate at 8000-11000 rpm, after high-speed dispersion for 8-15 hours, reduce the dispersion rate to 900-1500 rpm, then increase the temperature and keep the temperature constant at 90-100° C., then add ethylenediaminetetraacetic acid, disperse and react at a constant temperature for 10-18 hours, cool to room temperature, and centrifuge to obtain modified nano zirconium phosphate; The amino-containing silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N,N-diethyl-3-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; The preparation of the nano zirconium phosphate-copper manganese zinc oxide comprises the following steps: adding the modified nano zirconium phosphate to a high-speed dispersing kettle, then adding a copper manganese zinc salt solution, wherein the amount of the copper manganese zinc salt solution added is such that the modified nano zirconium phosphate is completely immersed, and the dispersion rate is controlled at 7000-12000 rpm, and after high-speed dispersing for 8-15 hours, the dispersing paddle is turned off, and the mixture is allowed to stand for immersion and complexation for 20-28 hours, and then centrifuged. The separated solid is placed in a muffle furnace, and the mixture is heated to 300-450° C. at a heating rate of 1-3° C. / min, and then calcined at a constant temperature for 2-5 hours to obtain the nano zirconium phosphate-copper manganese zinc oxide. The copper-manganese-zinc salt solution is a mixed aqueous solution of copper nitrate, manganese nitrate and zinc nitrate, wherein the mass ratio of copper nitrate, manganese nitrate, zinc nitrate and deionized water is 10-25:40-90:30-80:120-200; The preparation of the copper-aluminum-zirconium gel comprises the following steps: adding a mixed aqueous solution of aluminum trichloride and copper chloride, nano zirconium phosphate-copper manganese zinc oxide and polyvinyl pyrrolidone into a high-speed dispersion kettle, controlling the dispersion rate at 6000-9000 rpm, and after high-speed dispersion for 5-10 hours, reducing the dispersion rate to 900-1600 rpm, then dripping ammonia water with a mass concentration of 9-18 wt % at a speed of 0.1-0.9 g / min until the pH value of the solution reaches 9-10, thereby obtaining a copper-aluminum sol; and then adding a zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone. Adding into a high-speed dispersing kettle, controlling the dispersing rate at 6000-9000 rpm, after high-speed dispersing for 7-11 hours, reducing the dispersing rate to 900-1600 rpm, then dripping ammonia water with a mass concentration of 9-18wt% at a rate of 0.1-0.9g / min until the pH value of the solution reaches 9-10, to obtain zirconium sol, and then putting the copper aluminum sol and the zirconium sol into a mixing kettle at a mass ratio of 1:0.8-1.3, controlling the stirring rate at 900-1900 rpm, stirring and mixing for 5-14 hours, and standing and aging for 30-50 hours to obtain copper aluminum zirconium gel; The post-treatment comprises washing the copper-aluminum-zirconium gel with deionized water for 3 to 6 times, wherein the mass of the deionized water used for each washing is equal to the mass of the copper-aluminum-zirconium gel, and then washing the gel with anhydrous ethanol for 2 to 4 times, wherein the mass of the anhydrous ethanol used for each washing is equal to the mass of the copper-aluminum-zirconium gel, and then placing the gel in a dry and dust-free room temperature environment and airing it for 72 to 100 hours, and then placing the gel in an oven and drying it at 90 to 110° C. for 10 to 19 hours, and then placing the gel in a dry environment and cooling it to room temperature, and then grinding the gel in a dry environment into a powder of 300 to 800 meshes, and then placing the powder in a muffle furnace, heating it and maintaining the temperature at 700 to 950° C. at a heating rate of 2 to 10° C. / min, and then cooling the temperature to room temperature after calcining the gel at a constant temperature for 1 to 5 hours, to obtain a copper-based catalyst for hydrogen production by decomposing methanol.
2. The method for preparing a copper-based catalyst for producing hydrogen by cracking methanol according to claim 1, characterized in that: The particle size of the nano zirconium phosphate is 10-100 nm; The mass ratio of the nano zirconium phosphate, anhydrous ethanol and amino-containing silane coupling agent is 30-80:140-250:8-20; The mass ratio of the silane-coupled nano zirconium phosphate, deionized water and ethylenediaminetetraacetic acid is 20-60:90-180:8-25.
3. The method for preparing a copper-based catalyst for producing hydrogen by cracking methanol according to claim 1, characterized in that: The model of the polyvinyl pyrrolidone is K30, and the molecular weight is 43000-55000 g / mol; The mixed aqueous solution of aluminum chloride and copper chloride, wherein the mass fraction of aluminum chloride is 10-35wt%, and the mass fraction of copper chloride is 6-25wt%; The mixed aqueous solution of aluminum trichloride and cupric chloride, nano zirconium phosphate-copper manganese zinc oxide, and polyvinyl pyrrolidone are fed in a mass ratio of 80-190:20-100:0.5-4; The mass ratio of the zirconium oxychloride aqueous solution, nano magnesium oxalate powder, stabilizer Y2O3 and polyvinyl pyrrolidone is 60-160:2-9:0.5-1:0.5-2; In the zirconium oxychloride aqueous solution, the mass fraction of zirconium oxychloride is 10-40wt%; The particle size of the nano magnesium oxalate powder is 10-100 nm; The stabilizer Y2O3 is powdered nano Y2O3 with a particle size of 10-100 nm.
4. A copper-based catalyst for hydrogen production by cracking methanol prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The copper-based catalyst for methanol cracking to produce hydrogen has a copper oxide content of 7.5-14.3wt%, initial performance of methanol conversion rate of 97.1-98.2%, hydrogen selectivity of 98.2-98.9%, CO content in tail gas of 0.11-0.17%, and heat-resistant performance of methanol conversion rate of 96.5-97.7%, hydrogen selectivity of 97.6-98.3%, CO content in tail gas of 0.15-0.19%.
Citation Information
Patent Citations
Preparation method of methanol reforming hydrogen production catalyst with low copper content
CN115888754A
Pillared layered zirconium phosphate loaded nickel-based catalyst, preparation method and application thereof
CN106582736A
Highly-effectively copper-based catalyst for decomposing methanol to produce hydrogen
CN107824190A